Knowledge, attitude and practices of pediatricians at a level 3 government hospital on dental caries prevention among children - De Guzman, Jeanna Chriselle Z.; Flores, Kristine Kaye R.; Manrique, Ann Lexyz V.
INTRODUCTION: There were 87.4% of Filipinos that suffer from dental caries and it remains to be the most common infectious and chronic disease of children (National Monitoring and Evaluation Dental Survey, 2011). With pediatricians having the capability to reinforce oral hygiene measures in the earliest age possible, the researchers aim to determine the knowledge, attitude and practices of pediatricians at a level 3 government hospital on dental caries prevention among children.